The Effects of Executives on Corporate Tax Avoidance - Dyreng, Scott D.; Hanlon, Michelle; Maydew, Edward L. (The Accounting Review, 2010)
ABSTRACT: This study investigates whether individual top executives have incremental effects on their firms’ tax avoidance that cannot be explained by characteristics of the firm. To identify executive effects on firms’ effective tax rates, we construct a data set that tracks the movement of 908 executives across firms over time. Results indicate that individual executives play a significant role in determining the level of tax avoidance that firms undertake. The economic magnitude of the executive effects on tax avoidance is large. Moving between the top and bottom quartiles of executives results in approximately an 11 percent swing in GAAP effective tax rates; thus, executive effects appear to be an important determinant in firms’ tax avoidance.